\documentclass{article} % Import for matrices \usepackage{amsmath} % Import for therefore symbol \usepackage{amssymb} \begin{document} \title{Mathematics Assignment --- Matrices} \author{Ahmad Saalim Lone, 2019BCSE017} \date{05 May, 2020} \maketitle \section{Question 1} If \( A = \begin{bmatrix} 2 & -5 & -1 \\ -2 & -1 & 4 \end{bmatrix} B = \begin{bmatrix} 3 & 4 & 0 \\ 5 & -2 & 3 \end{bmatrix} \) find: \begin{enumerate} \item $A + B$ \item $2A + B$ \end{enumerate} \subsection{Part 1} \[ A + B = \begin{bmatrix} 2 + 1 & -5 + 4 & -1 + 0 \\ -2 + 5 & -1 -2 & 4 + 3 \end{bmatrix} \] \[ A + B = \begin{bmatrix} 3 & -1 & -1 \\ 3 & -3 & 7 \end{bmatrix} \] \subsection{Part 2} \[ 2A + B = \begin{bmatrix} 4 + 1 & -10 + 4 & -2 + 0 \\ -4 + 5 & -2 -2 & 8 + 3 \end{bmatrix} \] \[ 2A + B = \begin{bmatrix} 5 & -6 & -2 \\ 1 & -4 & 11 \end{bmatrix} \] \section{Question 2} If \( A = \begin{bmatrix} 1 & 2 & 3 \\ 4 & 5 & 6 \\ 7 & 8 & 9 \end{bmatrix} B = \begin{bmatrix} 1 & 0 & 2 \\ 2 & 1 & 2 \\ 5 & 2 & 3 \end{bmatrix} \), find $AB$. \[ AB = \begin{bmatrix} 1 & 2 & 3 \\ 4 & 5 & 6 \\ 7 & 8 & 9 \end{bmatrix} \begin{bmatrix} 1 & 0 & 2 \\ 2 & 1 & 2 \\ 5 & 2 & 3 \end{bmatrix} \] \[ AB = \begin{bmatrix} 1 \times 1 + 2 \times 2 + 3 \times 5 & 1 \times 0 + 2 \times 1 + 3 \times 2 & 1 \times 2 + 2 \times 2 + 3 \times 3 \\ 4 \times 1 + 5 \times 2 + 6 \times 5 & 4 \times 0 + 5 \times 1 + 6 \times 2 & 4 \times 2 + 5 \times 2 + 6 \times 3 \\ 7 \times 1 + 8 \times 2 + 9 \times 5 & 7 \times 0 + 8 \times 1 + 9 \times 2 & 7 \times 2 + 8 \times 2 + 9 \times 3 \end{bmatrix} \] \[ AB = \begin{bmatrix} 20 & 8 & 16 \\ 44 & 17 & 36 \\ 68 & 26 & 57 \end{bmatrix} \] \section{Question 3} If \( A = \begin{bmatrix} 1 & -2 & -3 \\ -4 & 2 & 5 \end{bmatrix} B = \begin{bmatrix} 2 & 3 \\ 4 & 5 \\ 2 & 1 \end{bmatrix} \), show that \(AB \ne BA\). Order of $A$ = $2\times3$ Order of $B$ = $3\times2$ Order of $AB$ = $rows \; of \; A \times columns \; of \; B$ = $2\times2$ Order of $BA$ = $rows \; of \; B \times columns \; of \; A$ = $3\times3$ Matrices of different order can't be equal. $\therefore AB \ne BA$ \section{Question 4} Show that \( A = \begin{bmatrix} 3 & 1 + 2i \\ 1-2i & 2 \end{bmatrix} \) is a hermitian. For a matrix to be hermitian, each element $a_{i,j}$ needs to be the complex conjugate of the element at $a_{j,i}$. In given matrix, we have \begin{itemize} \item \(a_{11} = 3\) \item \(a_{12} = 1 + 2i\) \item \(a_{21} = 1 - 2i\) \item \(a_{22} = 2\) \end{itemize} The conjugates are as follows \begin{itemize} \item \(\overline{a_{11}} = 3\) \item \(\overline{a_{12}} = 1 - 2i\) \item \(\overline{a_{21}} = 1 + 2i\) \item \(\overline{a_{22}} = 2\) \end{itemize} As we can see, \(\overline{a_{11}} = a_{11}\), \(\overline{a_{12}} = a_{21}\), \(\overline{a_{21}} = a_{12}\) and \(\overline{a_{22}} = a_{22}\). $\therefore A$ is hermitian. \section{Question 5} If \( A = \begin{bmatrix} 5 & 1 + i \\ -1 + i & 4 \end{bmatrix} \), show that ${(A^{\theta})}^{\theta}$ \[ A = \begin{bmatrix} 5 & 1 + i \\ -1 + i & 4 \end{bmatrix} \] \[ \overline{A^{\theta}} = \begin{bmatrix} 5 & - 1 - i \\ 1 + i & 4 \end{bmatrix} \] \[ {(A^{\theta})}^{\theta} = \begin{bmatrix} 5 & 1 + i \\ -1 + i & 4 \end{bmatrix} \] \[ \therefore {(A^{\theta})}^{\theta} = A \] \section{Question 6} $ A = \begin{bmatrix} 1 & 0 & -1 \\ 3 & 4 & 5 \\ 0 & -6 & -7 \end{bmatrix} $, find $ adj. A$ Adjoint of a matrix is the transpose of the cofactor matrix of the original matrix \[ Cofactor\;of\;A_{11} = \begin{vmatrix} 4 & 5 \\ -6 & -7 \end{vmatrix} = 2 \] \[ Cofactor\;of\;A_{12} = \begin{vmatrix} 3 & 5 \\ 0 & -7 \end{vmatrix} = -21 \] \[ Cofactor\;of\;A_{13} = \begin{vmatrix} 3 & 4 \\ 0 & -6 \end{vmatrix} = -18 \] \[ Cofactor\;of\;A_{21} = \begin{vmatrix} 0 & -1 \\ -6 & -7 \end{vmatrix} = -6 \] \[ Cofactor\;of\;A_{22} = \begin{vmatrix} 1 & -1 \\ 0 & -7 \end{vmatrix} = -7 \] \[ Cofactor\;of\;A_{23} = \begin{vmatrix} 1 & -1 \\ 0 & -6 \end{vmatrix} = -6 \] \[ Cofactor\;of\;A_{31} = \begin{vmatrix} 0 & -1 \\ 4 & 5 \end{vmatrix} = 4 \] \[ Cofactor\;of\;A_{32} = \begin{vmatrix} 1 & -1 \\ 3 & 5 \end{vmatrix} = 8 \] \[ Cofactor\;of\;A_{33} = \begin{vmatrix} 1 & 0 \\ 3 & 4 \end{vmatrix} = 4 \] \[ Cofactor\;Matrix = \begin{bmatrix} 2 & -21 & -18 \\ -6 & -7 & -6 \\ 4 & 8 & 4 \end{bmatrix} \] Adjoint matrix is the transpose of Cofactor Matrix. \[ \therefore adj.A = \begin{bmatrix} 2 & -6 & 4 \\ -21 & -7 & 8 \\ -18 & -6 & 4 \end{bmatrix} \] \section{Question 7} \( A = \begin{bmatrix} 0 & 0 & 1 \\ 0 & 1 & 0 \\ 1 & 0 & 0 \end{bmatrix} \), show that $A^{-1} = A$. We know that \[ A^{-1} = \frac{adj.(A)}{|A|} \] \begin{align*} Cofactor\;of\;A_{11} &= 0 \\ Cofactor\;of\;A_{12} &= 0 \\ Cofactor\;of\;A_{13} &= -1 \\ Cofactor\;of\;A_{21} &= 0 \\ Cofactor\;of\;A_{22} &= -1 \\ Cofactor\;of\;A_{23} &= 0 \\ Cofactor\;of\;A_{31} &= -1 \\ Cofactor\;of\;A_{32} &= 0 \\ Cofactor\;of\;A_{33} &= 0 \end{align*} \[ Cofactor\;Matrix = \begin{bmatrix} 0 & 0 & -1 \\ 0 & -1 & 0 \\ -1 & 0 & 0 \end{bmatrix} \] \[ adj.A = \begin{bmatrix} 0 & 0 & -1 \\ 0 & -1 & 0 \\ -1 & 0 & 0 \end{bmatrix} \] \[ |A| = \begin{vmatrix} 0 & 0 & 1 \\ 0 & 1 & 0 \\ 1 & 0 & 0 \end{vmatrix} = 1 \times \begin{vmatrix} 0 & 1 \\ 1 & 0 \end{vmatrix} = 1 \times -1 = -1 \] \[ A^{-1} = \frac{adj.A}{|A|} \] \[ A^{-1} = \begin{bmatrix} 0 & 0 & 1 \\ 0 & 1 & 0 \\ 1 & 0 & 0 \end{bmatrix} \] \[ \therefore A^{-1} = A \] \end{document}